(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study investigates the structural patterns of Indonesian-English code-switching in the Endgame podcast featuring host Gita Wirjawan and guest Baskara Putra. Code-switching, long observed in bilingual communities, is increasingly salient in digital media where it shapes public discourse and identity. The objective of this study is to identify the types, distribution, and grammatical integration of code-switching in a semi-formal podcast setting. Using a qualitative descriptive design with corpus-based elements, a purposive sample of 100 utterances containing switches from the Endgame video podcast was transcribed and analyzed. Guided by Poplack’s typology and Myers-Scotton’s Matrix Language Frame model, the results show that intra-sentential switching dominates, with English insertions clustering around abstract or globalized topics such as mental health and dystopia. English elements were consistently embedded into Indonesian grammar, sometimes morphologically adapted. These findings demonstrate that podcast code-switching is both structurally systematic and symbolically meaningful, highlighting its role in indexing cosmopolitan identities in contemporary Indonesia.